Pemberdayaan Kelompok Tani Kayu Bajak Kelurahan Kuranji melalui Pengelolaan Hama dan Penyakit penyebab Yellow Leaf Curl Virus pada Tanaman Terung - Lailatun Najmi; Jumsu Trisno; Yenny Liswarni (Buletin Dharmas Andalas, 2026)
Yellow disease in eggplant caused by a virus transmitted by Bemisia tabaci has become a serious threat to the sustainability of horticultural production in Padang City. The high dependence of farmers on chemical pesticides has the potential to induce pest resistance, environmental pollution, and health risks. This activity was conducted to enhance farmers’ capacity to recognize and control insect vectors of yellow disease through the application of eco-enzymes derived from fermented local plant organic waste as an environmentally friendly alternative control strategy. The methods applied included training, field demonstrations, mentoring, and the application of eco-enzymes in treatment plots, while chemical pesticides were applied in control plots. The results indicated that farmers’ knowledge increased by 80%. However, the incidence of yellow disease in the eco-enzyme treatment was 10% higher than that in the control, with disease severity being 3.11% higher. A production difference of 1.53 kg was observed, although plants treated with eco-enzymes exhibited better overall plant health, whereas 5% plant mortality was found in the control plots. It was concluded that eco-enzymes have not yet been effective as a single technology for controlling yellow disease in eggplant under field conditions. Therefore, the implementation of integrated pest management is required through the integration of natural enemies, the conservation of refugia plants, and the control of other pests such as shoot borer.